Prognostic Utility of Prechemoradiotherapy Albumin-to-Alkaline Phosphatase Ratio in Unresectable Locally Advanced Pancreatic Carcinoma Patients - Veysel Haksoyler; Erkan Topkan (Gastroenterology Research and Practice, 2021)
Background. We investigated the prognostic usefulness of prechemoradiotherapy (CRT) albumin-to-alkaline phosphatase ratio (AAPR) in unresectable locally advanced pancreatic adenocarcinoma (LAPAC) patients managed with definitive concurrent CRT (CCRT). Methods. A sum of 136 LAPAC patients who consecutively underwent definitive CCRT was retrospectively analyzed. The AAPR (serum albumin (g/dL)/serum alkaline phosphatase (IU/L)) was calculated by using the parameters obtained from the routine biochemistry tests on the first day of the CCRT. Ideal AAPR cutoff was sought by utilizing receiver operating characteristic (ROC) curve analysis. The primary and secondary endpoints were the impact of the AAPR on the overall survival (OS) and progression-free survival (PFS) results, respectively. Results. At a median follow-up of 14.8 months (range: 3.2-85.7), the median PFS and OS times were 7.5 (95% confidence interval (CI): 6.0-9.0) and 14.9 months (95% CI: 11.9-17.9), respectively. The ideal common AAPR cutoff was identified at the rounded 0.46 (area under the curve: 72.3%; sensitivity: 71.2%; specificity: 70.3%) point that dichotomized the patients into two groups: low AAPR (L-AAPR; N=71) and high AAPR (H-AAPR; N=65) groups, respectively. Comparative survival analyses showed that the L-AAPR cohort had significantly shorter median PFS (6.8 (95% CI: 5.7-7.9) versus 11.3 (95% CI: 9.9-12.7) months; P=0.005) and OS (12.8 (95% CI: 10.6-15.0) versus 19.2 (95% CI: 16.9-21.5) months; P=0.001) durations than their H-AAPR counterparts, separately. Albeit the N1-2 (P=0.004) and CA 19‐9>90 U/mL (P=0.008) were also found to be associated with inferior outcomes, yet the results of the multivariate analyses ascertained the L-AAPR as an independent indicator of diminished PFS (P=0.003) and OS (P=0.002) results. Conclusion. The present results proposed that the pretreatment AAPR<0.46 was a novel independent indicator of adverse PFS and OS in unresectable LAPAC patients undergoing definitive CCRT.